Dynamic Banking: A Reconsideration: Table 1 - Bhattacharya, Sudipto; Padilla, A. Jorge (Review of Financial Studies, 1996)
Financially intermediated and stock market consumption-investment allocations, with and without governmental interventions, are compared in a welfare sense in overlapping generation economies with (and without) shocks to agents’ intertemporal preferences. We first show that, in economies with preference shocks, governmental interventions subject to the same information requirements as those imposed on financial intermediaries, lead to stock market allocations that are not inferior to those attained under financial intermediation. Second, we argue that the necessary interventions are qualitatively no different from those required to implement stationary optimal allocations in OLG models without shocks to agents’ intertemporal consumption preferences.